A retrospective study of teenage pregnancy in a tertiary care hospital - Rudra, Samar; Bal, Himadri; Singh, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective of the study was to evaluate the maternal and fetal outcome of teenage pregnancy and find the effect of antenatal care on these teen mothers. Methods: A retrospective case study was performed over a period of three years. Data was retrieved from the hospital record. All teenage mothers (aged less than 19 years) delivering in the hospital were taken as cases. Consecutive two deliveries in the age group of 20 to 30 years meeting the inclusion and exclusion criteria were taken as control group. Various aspects of pregnancy outcome was recorded and analyzed. Results: The incidence of teenage pregnancy over the three years of study period was 4.33%. The occurrence of hypertensive disorders 32(9.4%) vs 36 (5.3%), p value < 0.01; IUGR 23 (6.7%) vs 11 (1.6%), p value < 0.01; preterm delivery 38 (11.2%) vs 18 (2.6%) p value < 0.01; and full term normal delivery 258 (75.9%) vs 563 (82.7%), (p value < 0.01 in the study group and control group respectively. Low birth weight babies 140 (41.2%) vs 63 (9.3%), p value < 0.01 and NICU admission 20 (5.8%) vs 9 (1.3%), p value < 0.01; were significantly higher in the study group. The comparison of various pregnancy outcomes according to the booking status of the teenage mothers finds significant improvement in most of the parameters in those who received adequate antenatal care. Conclusion: The pregnancy outcome of teenage mothers is poorer in comparison to 20 to 30 years age group in most of the parameters. Adequate antenatal care reduces the incidence of adverse pregnancy outcome significantly in the teen mothers.